การพัฒนารูปแบบผลิตภัณฑ์สินค้าชุมชนโดยใช้วิธีการวิจัยปฏิบัติการแบบมีส่วนร่วม กรณีศึกษา : ผลิตภัณฑ์ของใช้ในครัวเรือนบ้านคลองเดื่อพัฒนา ตำบลท่ามะนาว อำเภอชัยบาดาล จังหวัดลพบุรี - ธนัทพรรษรัตน์ ปัณณ์ณัช; สุรัสวดี ฉันทนา (Area Based Development Research Journal, 2015)
บทคัดย่อไม่สมบูรณ์ The Model Development of the Community Products by Participatory Action Research Method Case Study : Household products of Baan Khlong Dua Pattana in Tambon Tha Manao, Amphoe Chai Badan, Lopburi Province The research on The Model Development of the Community Products by Participatory Action Research Method, the Case study : Household products of Baan Khlong Dua Pattana in Tambon Tha Manao, Amphoe Chai Badan, Lopburi Province was aimed to (1) find out the problems and determine the needs in developing product models for community products of the entrepreneurs of Baan Khlong Dua Pattana (2) to develop a logo and graphics on the packaging of community products using participatory action research method (3) to survey the customer satisfaction towards the product models which have been developed. The sample groups consist of 10 people from Khlong Dua Pattana housewives group, 8 personnel of Tha Manao Sub-district Administrative Organization (SAO) who are associated with the seven learning centers in Tha Manao Community and two representatives from PTT Public Company Limited. Purposive sampling was used as a tool for sampling. And 80 selected consumers who were the field-trip attendants at the Tha Manao Sub-district Administrative Organization (SAO) and the people in the area, were chosen by means of accidental sampling to assess their satisfaction with the logo and graphics on the packaging. The instruments used in the research were: guideline questions for discussion groups to explore the issues and the needs to develop the models of community products, guideline questions for the comments of logo experts, guideline questions for the comments of the experts on graphical formats on the packaging, and the questionnaire created to assess the consumers’ satisfaction with the logos and graphics on the packaging. The data were analyzed by percentage, mean, and standard deviation. The results showed that before the research project, the community products of Baan Khlong Dua Pattana, Chai Badan District, Lopburi province, have simple forms; the product details were only described in text forms and typed on plain paper affixed to the products; some types of products were poured into used plastic water bottles, even without any labels resulting in lack of product credibility. Although there are organizations from both public and private sectors helping the group in designing logos and packaging graphics, they did not accept the designed logos because they did not participate in expressing their own ideas. When the research team entered the community and inquired the needs of the Khlong Dua Pattana group, they then would like the research team to design the logos and graphics on the packaging, using a participatory process, and the designs from such participatory process reflected clear identity of the group, resulting in the great recognition and immense pride of the group. From satisfaction surveys on logo designs, it showed a satisfaction with high level, and a satisfaction with the graphics on the packaging of household consumers products: shapes, colors appropriate to the nature of the products, clear illustrations which can add value, reliability, safety, beauty and prominence, it was found that the consumers’ satisfaction was at the high level .